The Mediator Role of Feelings of Guilt in the Process of Burnout and Psychosomatic Disorders: A Cross-Cultural Study - Figueiredo-Ferraz, Hugo; Gil-Monte, Pedro R.; Grau-Alberola, Ester; Ribeiro do Couto, Bruno (Frontiers in Psychology, 2021)
Burnout was recently declared by WHO as an “occupational phenomenon” in the International Classification of Diseases 11th revision (ICD-11), recognizing burnout as a serious health issue. Earlier studies have shown that feelings of guilt appear to be involved in the burnout process. However, the exact nature of the relationships among burnout, guilt and psychosomatic disorders remains unclear. The purpose of this study was to investigate the mediator role of feelings of guilt in the relationship between burnout and psychosomatic disorders, and perform a cross-cultural validation of the multi-dimensional model by Gil-Monte (2005) in two samples of teachers (Portuguese vs. Spanish). The study sample was composed of 1266 teachers, 1062 from Spain and 204 from Portugal. Burnout was measured by the Spanish Burnout Inventory. Hypotheses were tested together in a path model. The results obtained provide empirical evidence for the mediator role of guilt in the relationship between the Burnout syndrome and psychosomatic disorders in the sample of teachers from Spain and Portugal, and they contribute to the empirical validation of the model by Gil-Monte (2005, 2012). The results indicate that guilt should be incorporated as a symptom of burnout in order to identify individuals affected by burnout and profiles or types of burnout to differentiate it from other pathologies like depression.